Today (since 2010) - Yurtin, Vladimir; Ezhova, Larisa (project baikal, 2015)
Within the last five years the team of Irkutskrazhdanproject has worked out a number of interesting projects, such as a unique architectural and engineering solution for city environment – the 130 Quarter built by Irkutsk’s 350th anniversary in 2011, a new school for 600 students in Kultuk settlement, a water sports complex in Irkutsk and an international ethnocultural center Baigal. Irkutskgrazhdanproject is commissioned to improve the area planning scheme for the Irkutsk region and to work out regional design standards.